OPTIMIZING SUPPLY CHAIN RESILIENCE: STRATEGIES FOR MANAGING DISRUPTIONS - Anwar, Hairul; Kadafi, Muhammad Amin; Judiarni, Justina Ade; ZA, Saida Zainurossalamia (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores key strategies for improving supply chain resilience in the face of disruption across a range of industries. Using a Systematic Literature Review (SLR) approach, this research analyzes various literature that discusses technology, supplier diversification, collaboration, and capacity management as strategies for facing global challenges such as pandemics, natural disasters, and geopolitical tensions. The research results show that the adoption of digital technologies and close collaboration with suppliers has proven effective in increasing resilience, while the Just-in-Time model is often vulnerable to major disruptions. This research provides important implications for supply chain management practitioners to adopt more adaptive and resilient strategies.